Using Benthic Diatom to Assess the Success of Batch Culture System Phytoremediation Process of Water Irrigation - Retnaningdyah, Catur; Arisoesilaningsih, Endang (Journal of Tropical Life Science, 2018)
Diatoms or phytobenthic are often used as bio-indicators of water quality in freshwater ecosystems such as rivers, but have never been used for monitoring the quality of artificial water ecosystems. The objective of this research is to use the diatom as a bioindicator for measurement the success of phytoremediation process of irrigation water that has status hyper-eutrophic and is polluted from organic materials using polyculture of various local hydromacrophytes through batch culture system. This experimental study was conducted in a greenhouse through planting some local emergent, submerged and floating leaf hydromacrophytes on a 30 L bucket with a given substrate from sand and gravel. The experiment used a completely randomized design with two treatment included phytoremediation model and control in the form of substrate without hydromacrophyte which repeated three times at the same time. The success of phytoremediation model was determined through some biotic diatoms indices (Percentage Pollution Tolerant Value/%PTV, Tropical Diatom Index/TDI and Shannon Wiener Diversity Index) as bioindicator and the improved water physics chemical quality on days 0, six, and 13 after incubation. The results showed that phytoremediation process using polyculture hydromacrophytes through batch culture system for 13 days significantly improving the quality of irrigation water. Based on some biotic diatom indices, the water was improved from heavily organic pollution to moderately organic pollution (%PTV), from hypereutrophic to become eutrophic (TDI) and from moderately polluted become slightly polluted (Shannon Wiener Diversity Index). This results also supported from water physico-chemical parameters. Poly-culture of some local hydromacrophytes for six days significantly decreased the organic matter content of irrigation water was reflected from the decrease concentration of Biochemical Oxygen Demand/BOD (14.79 mg/L to 3.61 mg/L), Total Suspended Solid/TSS (14.6 mg/L to 0.08 mg/L), turbidity (19.97 NTU to 1.46 NTU), nitrate (1.44 mg/L to 0.03 mg/L), orthophosphate (0.24 mg/L to 0.042 mg/L), Total Kjeldahl Nitrogen (TKN) (0.93 mg/L to 0.68 mg/L), and free chlorine (0.09 mg/L to 0.05 mg/L), while concentration of Chemical Oxygen Demand (COD) decreased significantly 13 days after incubation from 48.3 mg/L to18.2 mg/L.